2000
DOI: 10.1016/s0014-5793(00)01697-5
|View full text |Cite
|
Sign up to set email alerts
|

The heterotrimeric Thermus thermophilus Asp‐tRNAAsn amidotransferase can also generate Gln‐tRNAGln

Abstract: Thermus thermophilus strain HB8 is known to have a heterodimeric aspartyl-tRNA(Asn) amidotransferase (Asp-AdT) capable of forming Asn-tRNA(Asn) [Becker, H.D. and Kern, D. (1998) Proc. Natl. Acad. Sci. USA 95, 12832-12837]. Here we show that, like other bacteria, T. thermophilus possesses the canonical set of amidotransferase (AdT) genes (gatA, gatB and gatC). We cloned and sequenced these genes, and constructed an artificial operon for overexpression in Escherichia coli of the thermophilic holoenzyme. The over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 9 publications
2
46
0
1
Order By: Relevance
“…Based on our functional studies, it is unlikely that this At5g64440 gene product functions as a glutamyl-tRNA amidotransferase, and this activity has not been attributed to membrane-bound mammalian FAAH enzymes. Additionally, in plants these glutamyltRNA amidotransferases are localized in the stroma of chloroplasts as soluble, oligomeric complexes of multiple subunits (45,46). In fact, nuclear-encoded, chloroplast-localized orthologues of the glutamyl-tRNA amidotransferase subunits have been cloned from Arabidopsis and expressed/characterized by the Soll group (GenBank TM accession numbers, AF241841, AF240465, AF239836, and AF224745), and these proteins share less than 24% amino acid sequence identity with the At5g64440 NAE amidohydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our functional studies, it is unlikely that this At5g64440 gene product functions as a glutamyl-tRNA amidotransferase, and this activity has not been attributed to membrane-bound mammalian FAAH enzymes. Additionally, in plants these glutamyltRNA amidotransferases are localized in the stroma of chloroplasts as soluble, oligomeric complexes of multiple subunits (45,46). In fact, nuclear-encoded, chloroplast-localized orthologues of the glutamyl-tRNA amidotransferase subunits have been cloned from Arabidopsis and expressed/characterized by the Soll group (GenBank TM accession numbers, AF241841, AF240465, AF239836, and AF224745), and these proteins share less than 24% amino acid sequence identity with the At5g64440 NAE amidohydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…In other bacteria, archaea, and some organelles however, AspRS is a non-canonical, non-discriminating enzyme (ND-AspRS) that generates both AsptRNA Asp and the misacylated Asp-tRNA Asn (5)(6)(7)12,3,14). This Asp-tRNA Asn is converted to Asn-tRNA Asn by a glutamine-dependent Asp-tRNA Asn /Glu-tRNA Gln amidotransferase (Asp/ Glu-Adt) (26,27,9,28,12). ND-AspRS is most commonly found in organisms lacking asparaginyl-tRNA synthetase (AsnRS) and in these cases, the combination of ND-AspRS and Asp/Glu-Adt provides the sole route for Asn-tRNA Asn biosynthesis and, in some cases, for asparagine biosynthesis as well (7,29).…”
Section: Introductionmentioning
confidence: 99%
“…Genome analyses of bacteria and archaea have revealed that the presence of the ND-AspRS is always accompanied by the occurrence of the heterotrimeric GatCAB amidotransferase, an enzyme capable of converting the misacylated Asp-tRNA Asn to Asn-tRNA Asn (2,5,19). Presumably, this is to avoid introducing the misacylated Asp-tRNA Asn into an organism's translational apparatus and potentially endangering protein synthesis.…”
mentioning
confidence: 99%